Legal determinants of the effectiveness of spatial planning in Poland - Zachariasz, Igor (Journal of Public Governance, 2013)
Spatial planning in Poland does not help to organize the activities of private and public entities. Decisions made in general and special spatial planning acts are not associated with any financial resources of the public and private sector; they do not guarantee that the development of an area will be carried out in accordance with the planning’s requirements in a specified time. The planning process, contrary to the proclaimed doctrinal declarations, is not balancing all the rights and obligations of the private and public entities in land use.